2002
DOI: 10.2527/2002.80184x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricted feeding, low-energy diet, and implantation of trenbolone acetate plus estradiol on growth, carcass traits, and circulating concentrations of insulin-like growth factor (IGF)-I and IGF-binding protein-3 in finishing barrows

Abstract: Effects of restricted feeding (80% ad libitum), feeding a low-energy diet containing 84% DE (2.95 Mcal/kg) of the control diet, and implantation of Revalor H (140 mg trenbolone acetate plus 14 mg estradiol-17beta) on growth, carcass traits, and serum concentrations of insulin-like growth factor (IGF)-I and IGFbinding protein-3 (IGFBP-3) were studied in crossbred finishing barrows beginning from 59 +/- 0.9 kg of body weight. Blood samples were taken every 3 wk and the animals were slaughtered at approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
3
41
2
2
Order By: Relevance
“…In spite of its low palatability (Domínguez, 1995), swine adapted to the new ingredient of the diets even on the highest level of inclusion. It is known that swine increase daily feed intake when a progressive dilution of the ration with inert or indigestible material is done (Chadd, 1990;Lee et al, 2002), this was different the results observed here, where no intake counterbalance occurred. In spite of the presence of substances that decreased the palatability, the high water retention capacity of citrus pulp could maintain the physical satiate for longer time, lowering the stimulus to feed (Kyriazakis and Emmans, 1995).…”
Section: Trialcontrasting
confidence: 57%
“…In spite of its low palatability (Domínguez, 1995), swine adapted to the new ingredient of the diets even on the highest level of inclusion. It is known that swine increase daily feed intake when a progressive dilution of the ration with inert or indigestible material is done (Chadd, 1990;Lee et al, 2002), this was different the results observed here, where no intake counterbalance occurred. In spite of the presence of substances that decreased the palatability, the high water retention capacity of citrus pulp could maintain the physical satiate for longer time, lowering the stimulus to feed (Kyriazakis and Emmans, 1995).…”
Section: Trialcontrasting
confidence: 57%
“…Nesse caso, apesar de a casca de arroz apresentar características sensoriais negativas, pelo menos para o paladar humano (Vicenzi et al, 2001), não houve redução do consumo das dietas contendo esse subproduto. O segundo aspecto é a capacidade dos animais em manter o consumo energético independentemente da concentração calórica das dietas (Lee et al, 2002), o que não ocorreu neste trabalho, pois o consumo energético reduziu na mesma proporção da restrição energética nas dietas. É possível que a própria capacidade gástrica dos animais tenha limitado o consumo das dietas mais diluídas, dado seu maior volume, promovido pela inclusão da casca de arroz.…”
Section: Resultsunclassified
“…Currently, the dietary energy densities for finishing pigs recommended by major institutes worldwide are fairly variable ranging from as low as 3.1 Mcal DE/kg (ARC, 1981;SCA, 1987) to 3.3 Mcal (JRC, 1998) or 3.4 Mcal DE/kg (NRC, 1998RDA, 2007), although actual DE values of domestically available commercial finisher diets are mostly greater than 3.4 Mcal/kg. Lee et al (2000Lee et al ( , 2002 have reported that lean-type pigs fed a low-energy diet containing 2.95 Mcal DE/kg had a lesser growth rate than those fed a high-energy diet containing 3.5 Mcal DE/kg during a finishing period between 60-and 105-kg body weights. More lately, Lee et al (2007) have also reported that a 'medium'-and a 'high'-energy diets containing 3.2 and 3.4 Mcal DE/kg, respectively, were comparable in feed efficiency as well as in their effects on growth and carcass quality characteristics of lean-type pigs fed the respective diets from 90 kg to 125 or 135 kg.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was therefore undertaken to investigate the effects of dietary energy level on growth and its efficiency as well as carcass quality traits of non-lean finishing pigs at the optimal slaughter weight. (Lee et al, 2002;Park et al, 2007).…”
Section: Introductionmentioning
confidence: 99%